Gender Differences in the Relationship Between Sexual Activity and Dating Violence: The Role of Satisfaction, Jealousy, and Self-control - Powers, Ráchael A. (Journal of interpersonal violence, 2022)
While research has shown that sexual intercourse within a relationship is positively associated with physical intimate partner violence (IPV) perpetration, particularly among young adults, whether well-known correlates of IPV moderate this relationship and whether these effects are gendered is less known. We draw on data from the International Dating Violence Study (2001?2006; n = 5,502) to more thoroughly explore sexual activity in a relationship on the risk for dating violence perpetration among college students in heterosexual relationships. First, the relationship between sexual activity and physical IPV is examined. Second, this study examines the role of sexual satisfaction/disagreement on IPV among sexually active participants as a potential mechanism by which sexual activity impacts IPV. Third, this study examines whether jealousy and self-control, two well-known correlates of IPV, moderate the relationship between sexual activity and IPV. For all analyses, gendered effects were examined. We found that sexual activity was positively related to overall and severe (i.e., potentially injurious) IPV perpetration and the effects were comparable between men and women. Likewise, although there was gender symmetry in the main effects of jealousy, results demonstrate that the interaction between intimacy and jealousy was gendered. Conversely, self-control was related to IPV comparably for men and women but did not moderate the effects of intimacy. Sexual satisfaction was unrelated to IPV perpetration for men and women, but women who report disagreement over frequency of intercourse reported higher offending. The theoretical implications of the current study are discussed as well as avenues for prevention and intervention programming, including collaborative, campus-based approaches to both violence prevention, healthy relationships, and sexual decision-making.